A critique of liberal cynicism Peter Sloterdijk, Judith Butler, and critical liberalism - Barnes, Will (William H.) (Lexington Books, 2022)
"Focusing on the philosophical work of Judith Butler and Peter Sloterdijk, A Critique of Liberal Cynicism diagnoses-and proposes an immanent critique of-a form of cynicism dominant in popular and academic culture"--